SISTEM IJTIHA DALAM HUKUM ISLAM (Metodologi Pembaruan Ibnu Taimiyah) - Hamang, M. Nasri (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2010)
This article explores the ijtihad system in Islamic law with special reference to ibn Taimiyahâs reform method. This study reveals that ibn Taimiyah is one of proponents of reform in ijtihad methodology. In this methodology, he frequently follows the line of Hanbalite system, and neglects three other systems, Hanafite, Malikite, and Syafiâite. He even produces some works according to his own methodology. Ibn Taimiyah lays so much emphasis on the application of ijtihad methodology based on Qurâan and Sunnah, yet does not neglect ijmaâ, qiyas, and maslahah mursalah, with strict requirement. He is different from Abu Hanifah who emphasizes the application of istihsan and âurf, from Malik who emphasizes maslahah mursalah, and from Syafiâi who prefers the istidlal methodology. Actually, ibn Taimiyah appreciates the rational faculty in analizing the texts (nash). According to him, the usage of rational reasoning makes Islamic law logical. In comprehending religious truth, especially related to natural phenomena and social life, ibn Taimiyah is an empiricist and rationalist. This in turn endorses the scientific experiment and direct observation.